PENYELAMATAN ARSIP VITAL DAN ARSIP BERNILAI GUNA PERMANEN DARI MUSIBAH DAN BENCANA - Sumrahyadi, Sumrahyadi (BACA: Jurnal Dokumentasi dan Informasi, 2009)
Records, particularly, vital records as corporate memory are very important to run their activities and as backbone for organizations. As well archives which are kept in the National Archives of Indonesia for records permanent nationally and Archives (and Library) Institutions for local government, they kept for the next generation and national accountability permanently. For those important functions, they have to be maintained and safeguarded from natural disaster or other human error otherwise we lost evidence forever. For these reasons, we have to be aware to protect them from the possibility of destruction with several prevention and several steps.